2009
DOI: 10.1074/jbc.m109.012476
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the Functional Boundaries and Secondary Structure of the Mouse Mammary Tumor Virus Rem-responsive Element

Abstract: Mouse mammary tumor virus (MMTV) is a complex retrovirus that encodes at least three regulatory and accessory proteins, including Rem. Rem is required for nuclear export of unspliced viral RNA and efficient expression of viral proteins. Our previous data indicated that sequences at the envelope-3 long terminal repeat junction are required for proper export of viral RNA. To further map the Rem-responsive element (RmRE), reporter vectors containing various portions of the viral envelope gene and the 3 long termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 55 publications
2
51
0
Order By: Relevance
“…Both GFPRem and GFP-SP fusions are functional in a reporter assay that measures a postexport function (e.g., translation) (5). Rem-dependent reporter activity requires the NLS as well as the presence of a Rem-responsive element (RmRE) in the reporter construct (1,6). Together, these data suggest that SP binds to MMTV RNA in the nucleolus for Rem-dependent reporter activity.…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…Both GFPRem and GFP-SP fusions are functional in a reporter assay that measures a postexport function (e.g., translation) (5). Rem-dependent reporter activity requires the NLS as well as the presence of a Rem-responsive element (RmRE) in the reporter construct (1,6). Together, these data suggest that SP binds to MMTV RNA in the nucleolus for Rem-dependent reporter activity.…”
mentioning
confidence: 67%
“…1E). Previous results have shown that Rem activity in the pHMRluc assay measures a postexport function that requires both a nuclear localization signal and a binding site (RmRE) localized at the env-U3 border of MMTV RNA (1,6). Both the NLS and the RNA-binding motif are localized within SP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations